INTELLECTUAL CAPITAL AND ITS IMPACT ON ACHIEVING COMPETITIVE ADVANTAGE BETWEEN COMPANIES – FIELD STUDY IN THE IRAQ GREEN RANCHES COMPANY - Lecture – Abdul Hassan Rahim (Scholars Digest Publishing, 2023)
In recent years, intellectual capital has been used for many purposes that other types of capital were unable, including achieve the competitive advantage of the company that possesses the elements of human resources that are characterized by qualifications, experience, creativity and innovations that other companies are unable to provide. Therefore, the goal of the current research is answering questions such as whether our Iraqi companies, including the company under study, have an appropriate amount of interest in capital encouraging and preserving such elements. The research hypotheses have been developed on the basis that possessing intellectual capital is the best way to enable the company to compete with its peers in the market, and it is assumed that working to achieve intellectual capital in the company is not a difficult or impossible process if it is better implement its requirements and provide a good system of motivation and standards a good choice of human resources who are able to own it. The researcher has proven the validity of the hypotheses and that the Iraqi institutions are in need of understanding and comprehending the concept of intellectual capital, its contents and requirements, and the study has proven that the actual factor influencing the competition between companies is actually the human capacity for creativity and development. The researcher also found that the company under study is one of the few companies that seek to attach importance to this subject It deserves it to retain its creative elements, and it has allocated the necessary resources to achieve this and established a branch for it specialized in training, reinforced with foreign expertise to provide the necessary expertise to achieve the aforementioned goal towards achieving the competitive advantages that it aspires to.
Keywords: Intellectual capital, human resource accounting, human capital.